Ineffective controls on capital inflows under sophisticated financial markets: Brazil in the nineties - Bernardo S. de M. Carvalho; Márcio G. P. Garcia (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2006)
We analyze the Brazilian experience in the 1990s to access the effectiveness of controls on capital inflows in restricting financial inflows and changing their composition towards long term flows. Econometric exercises (VARs) lead us to conclude that controls on capital inflows were effective in deterring financial inflows for only a brief period, from two to six months. The hypothesis to explain the ineffectiveness of the controls is that financial institutions performed several operations aimed at avoiding capital controls. We then conducted interviews with market players in order to provide several examples of the financial strategies that were used in this period to invest in the Brazilian fixed income market while bypassing capital controls. The main conclusion is that controls on capital inflows, while they may be desirable, are of very limited effectiveness under sophisticated financial markets. Therefore, policy-makers should avoid spending the scarce resources of bank supervision trying to implement them and focus more in improving economic policy.
Keywords: E44; F32; F34; F36; G15; 330; Kapitalverkehrskontrolle; Kapitalimport; Brasilien